ASSOTIATION-GENETIC STUDY OF POLYMORPHISM G-105A SEPS1 GENE IN MALE INFERTILITY - N. G. Kul'chenko; G. I. Myandina; Hasan Alhedjoj (Исследования и практика в медицине)
About 30 million men in the world are infertile. Genetic factors are the cause of 15-30% of cases of pathospermia.Purpose. To study the influence of polymorphism G-105A (rs28665122) of SEPS1 gene on the development of pathospermia among men with infertility inMoscow region.Patients and methods. There were examined 138 men. All patients were divided on 2 groups: the first (n = 70) – patients with pathospermia, the second (control) – fertile men (n = 68). All patients underwent clinical examination: analysis of spermograms, determination of hormonal profile, ultrasound of scrotum organs. We performed a genetic analysis of peripheral blood leukocyte DNA in patients of both groups. All DNA samples were studied for the presence of polymorphism G-105A (rs28665122) SEPS1 gene using polymerase chain reaction methods and the analysis of restriction fragments length polymorphism (PCR-RFLP).Results. All patients of the first group suffered from severe infertility. Of these, 26 (37.14%) men had asthenozoospermia, 23 (32.85%) men with teratozoospermia, 21 (30.0%) azoospermia. A clinical study of patients of the first group did not reveal any serious deviations from the norm, so we were installed they idiopathic infertility. Our study of gene polymorphism SEPS1 showed that patients with pathospermia have allele -105А (genotypes GA+AA) a twice as often as in the control group of fertile men (48.57% и 27.94%, respectively, p < 0.001). Conclusion. Polymorphism G*-105A SEPS1* gene may beused for screening of infertility in men.